Statistical Models for Stability Analysis in Watermelon - R Venugopalan; M Pitchaimuthu (Journal of Horticultural Sciences, 2009)
Fourteen promising F1 hybrids of watermelon namely IIHR-188 X IIHR-118, IIHR 114 X IIHR 118 , IIHR 119 X IIHR- 20-1, Arka Manik X IIHR 46, IIHR 43 X IIHR 46, Arka Manik X IIHR-188, Arka Jyothi, NS-295, Kushboo, Madhubala, Apoorva, CWH-7 and Riya were evaluated in experimental plots of Division of Vegetable Crops, Indian Institute of Horticultural Research, Bangalore during 2002-04. Information about biometrical characters such as fruit length (cm), fruit girth (cm), days to first male flower opening&female flower opening, rind thickness(cm) and TSS (%) along with yield (t ha-1), were used to develop stability models to identify stable hybrid(s) for a wide range for cultivation. Stability models thus developed indicated that two hybrids, viz., Arka Jyothi (with yield potential of 75.91 t ha-1) across the years and NS-295 (64.25 t ha-1) were stable for a wide range for cultivation. Statistical measures of stability, viz., regression coefficient, deviation from regression co-efficient and ecovalence measures, were worked out and utilized for grouping of hybrids into different categories based on their cumulative performance over the years.